Profile Analysis of Faculty-Researchers in STEM Education in a Philippine University - Bryan Mallillin Nozaleda; Jhoanna Battung Calubaquib (Universitas Negeri Makassar, 2020)
The aim of this study is to create a deeper analysis of the individual backgrounds of higher education educators who are involved in research on Science, Technology, Engineering, and Mathematics (STEM) in a state university in the Philippines. To meet this objective, the study used a quantitative research design utilizing descriptive analytical tools. The participants were 104 teachers from the five campuses of the university that offers STEM undergraduate programs. Essentially, the study concludes that from the data gathered, the university has a gender-neutral participation in terms of doing research. The profile further creates an image that doing research in the university is not prejudicial to teachers with lower academic ranks. Meanwhile, the STEM educators have started doing research after some years of teaching and on average, teachers spend half of their academic experience in doing research. On another note, almost all of the respondents had more teaching loads than doing research and had less than four years of research experience on average. Based on these findings, for a university aiming to build a strong research culture, it is recommended to apportion more work time for conducting research in addition to teaching and strengthen the university research support to the faculty members by providing them opportunities to participate in research conferences, publish research outputs, and conduct research in the university.